Evaluasi Guru Penggerak Perspektif Guru PAI Berbasis CIPP di OKU Timur Sumatera Selatan - Putri Winarsih; Suwadi; Rahmadi Bagus Wijaya; Reza Yunita (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This study aims to evaluate the Teacher Leader Program from the perspective of Islamic Religious Education (PAI) teachers in East OKU Regency, South Sumatra, using the CIPP (Context, Input, Process, Product) evaluation model. This study used a qualitative approach with a case study design to explore the experiences, perspectives, and challenges faced by PAI teachers in participating in the program. Data collection techniques were conducted through in-depth interviews with participating teachers, participant observation during learning activities, and documentation review related to program implementation. The research subjects were PAI teachers who were actively involved in the Teacher Leader Program in the region. The results showed that the Teacher Leader Program had a positive impact on improving the pedagogical capacity, leadership, and professional reflection of PAI teachers. In terms of context, a clear need was identified for training that better aligns with the characteristics of Islamic religious education. In terms of input, participant engagement was quite good, but there were still obstacles in the form of limited institutional support from schools. The process aspect showed increased innovation in learning practices, while the product aspect reflected the development of teacher competencies in leading learning and fostering a collaborative culture. However, the study also identified challenges, including a misalignment of training materials with the specific needs of PAI and a lack of sustainability in mentoring. Therefore, this study recommends adjusting the curriculum and training methods, increasing institutional support, and strengthening program sustainability. With these steps, the Teacher Mover Program is expected to be more effective in empowering Islamic Religious Education teachers as agents of educational change in East OKU Regency. Abstrak Penelitian ini bertujuan untuk mengevaluasi Program Guru Penggerak dari perspektif guru Pendidikan Agama Islam (PAI) di Kabupaten OKU Timur, Sumatera Selatan, dengan menggunakan model evaluasi CIPP (Context, Input, Process, Product). Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus agar dapat menggali pengalaman, pandangan, serta tantangan yang dihadapi guru PAI dalam mengikuti program tersebut. Teknik pengumpulan data dilakukan melalui wawancara mendalam dengan guru peserta, observasi partisipatif dalam aktivitas pembelajaran, serta telaah dokumentasi terkait implementasi program. Subjek penelitian adalah guru PAI yang secara aktif terlibat dalam Program Guru Penggerak di wilayah tersebut. Hasil penelitian menunjukkan bahwa Program Guru Penggerak memiliki dampak positif dalam meningkatkan kapasitas pedagogik, kepemimpinan, dan refleksi profesional guru PAI. Pada aspek konteks, ditemukan kebutuhan nyata akan pelatihan yang lebih sesuai dengan karakteristik pendidikan agama Islam. Pada aspek input, keterlibatan peserta cukup baik, namun masih ada kendala berupa keterbatasan dukungan institusional dari sekolah. Aspek proses menunjukkan adanya peningkatan inovasi dalam praktik pembelajaran, sementara aspek produk mencerminkan berkembangnya kompetensi guru dalam memimpin pembelajaran dan menumbuhkan budaya kolaboratif. Meskipun demikian, penelitian juga menemukan tantangan, antara lain ketidakselarasan materi pelatihan dengan kebutuhan spesifik PAI serta kurangnya keberlanjutan dalam pendampingan. Oleh karena itu, penelitian ini merekomendasikan perlunya penyesuaian kurikulum dan metode pelatihan, peningkatan dukungan kelembagaan, serta penguatan keberlanjutan program. Dengan langkah tersebut, Program Guru Penggerak diharapkan dapat lebih optimal dalam memberdayakan guru PAI sebagai agen perubahan pendidikan di Kabupaten OKU Timur.